Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Certainly! Let's work through this step-by-step to determine the \( p+q \)-th derivative of the function \( y = x^p (1 + x)^q \).
First, let's define the given functions:
[tex]\[ u = x^p \][/tex]
[tex]\[ v = (1 + x)^q \][/tex]
We will use the formula for the \( n \)-th derivative of the product of \( u \) and \( v \):
[tex]\[ y^{(n)} = \sum_{k=0}^{n} \binom{n}{k} u^{(n-k)} v^{(k)} \][/tex]
Here, we are interested in \( y^{(p+q)} \), so \( n = p + q \).
### Step-by-Step Calculation
1. Determine \( u \) and its derivatives:
[tex]\[ u = x^p \][/tex]
[tex]\[ u^{(n)} = \frac{d^n}{dx^n} (x^p) \][/tex]
For \( u = x^p \), the \( n \)-th derivative \( u^{(n)} \) is zero for \( n > p \). For \( n \leq p \):
[tex]\[ u^{(n)} = \frac{d^n}{dx^n} (x^p) = \frac{p!}{(p-n)!} x^{p-n} \][/tex]
2. Determine \( v \) and its derivatives:
[tex]\[ v = (1 + x)^q \][/tex]
[tex]\[ v^{(n)} = \frac{d^n}{dx^n} ((1 + x)^q) \][/tex]
For \( v = (1 + x)^q \), the \( n \)-th derivative \( v^{(n)} \) is given by:
[tex]\[ v^{(n)} = \frac{q!}{(q-n)!} (1+x)^{q-n} \][/tex]
3. Apply the product rule formula:
[tex]\[ y^{(p+q)} = \sum_{k=0}^{p+q} \binom{p+q}{k} u^{(p+q-k)} v^{(k)} \][/tex]
Now, let’s break down the terms for \( u^{(p+q-k)} \) and \( v^{(k)} \):
- For \( k > p \), \( u^{(p+q-k)} = 0 \) because the derivative \( u^{(n)} \) is zero when \( n > p \).
- For \( k \leq p \), \( u^{(p+q-k)} = \frac{p!}{(p - (p+q-k))!} x^{p - (p+q-k)} = \frac{p!}{(q-k)!} x^{p+q-k} \).
So, when we sum up these terms:
[tex]\[ y^{(p+q)} = \sum_{k=0}^{p} \binom{p+q}{k} \frac{p!}{(q-k)!} x^{p+q-k} \frac{q!}{(q-k)!} (1 + x)^{q-k} \][/tex]
Combining constants and simplifying:
[tex]\[ y^{(p+q)} = \sum_{k=0}^{p} \binom{p+q}{k} \frac{p! q!}{(q-k)!(q-k)!} x^{p+q-k} (1 + x)^{q-k} \][/tex]
The general form can be complex to express in a simplified term without specific values for \( p \) and \( q \). However, this approach gives us the detailed step-by-step method used to calculate higher-order derivatives.
### Summary
To calculate \( y^{(p+q)} \) for \( y = x^p (1 + x)^q \), we use:
[tex]\[ y^{(p+q)} = \sum_{k=0}^{p} \binom{p+q}{k} \frac{p! q!}{(q-k)!(q-k)!} x^{p+q-k} (1 + x)^{q-k} \][/tex]
This involves calculating the derivatives of the individual functions and then using the product rule to sum up the appropriate terms.
First, let's define the given functions:
[tex]\[ u = x^p \][/tex]
[tex]\[ v = (1 + x)^q \][/tex]
We will use the formula for the \( n \)-th derivative of the product of \( u \) and \( v \):
[tex]\[ y^{(n)} = \sum_{k=0}^{n} \binom{n}{k} u^{(n-k)} v^{(k)} \][/tex]
Here, we are interested in \( y^{(p+q)} \), so \( n = p + q \).
### Step-by-Step Calculation
1. Determine \( u \) and its derivatives:
[tex]\[ u = x^p \][/tex]
[tex]\[ u^{(n)} = \frac{d^n}{dx^n} (x^p) \][/tex]
For \( u = x^p \), the \( n \)-th derivative \( u^{(n)} \) is zero for \( n > p \). For \( n \leq p \):
[tex]\[ u^{(n)} = \frac{d^n}{dx^n} (x^p) = \frac{p!}{(p-n)!} x^{p-n} \][/tex]
2. Determine \( v \) and its derivatives:
[tex]\[ v = (1 + x)^q \][/tex]
[tex]\[ v^{(n)} = \frac{d^n}{dx^n} ((1 + x)^q) \][/tex]
For \( v = (1 + x)^q \), the \( n \)-th derivative \( v^{(n)} \) is given by:
[tex]\[ v^{(n)} = \frac{q!}{(q-n)!} (1+x)^{q-n} \][/tex]
3. Apply the product rule formula:
[tex]\[ y^{(p+q)} = \sum_{k=0}^{p+q} \binom{p+q}{k} u^{(p+q-k)} v^{(k)} \][/tex]
Now, let’s break down the terms for \( u^{(p+q-k)} \) and \( v^{(k)} \):
- For \( k > p \), \( u^{(p+q-k)} = 0 \) because the derivative \( u^{(n)} \) is zero when \( n > p \).
- For \( k \leq p \), \( u^{(p+q-k)} = \frac{p!}{(p - (p+q-k))!} x^{p - (p+q-k)} = \frac{p!}{(q-k)!} x^{p+q-k} \).
So, when we sum up these terms:
[tex]\[ y^{(p+q)} = \sum_{k=0}^{p} \binom{p+q}{k} \frac{p!}{(q-k)!} x^{p+q-k} \frac{q!}{(q-k)!} (1 + x)^{q-k} \][/tex]
Combining constants and simplifying:
[tex]\[ y^{(p+q)} = \sum_{k=0}^{p} \binom{p+q}{k} \frac{p! q!}{(q-k)!(q-k)!} x^{p+q-k} (1 + x)^{q-k} \][/tex]
The general form can be complex to express in a simplified term without specific values for \( p \) and \( q \). However, this approach gives us the detailed step-by-step method used to calculate higher-order derivatives.
### Summary
To calculate \( y^{(p+q)} \) for \( y = x^p (1 + x)^q \), we use:
[tex]\[ y^{(p+q)} = \sum_{k=0}^{p} \binom{p+q}{k} \frac{p! q!}{(q-k)!(q-k)!} x^{p+q-k} (1 + x)^{q-k} \][/tex]
This involves calculating the derivatives of the individual functions and then using the product rule to sum up the appropriate terms.
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.